Pool systems and methods for making and using same - Lan, Chao Long (2019)
Embodiments of the present disclosure provide an improved pool. Embodiments of the present disclosure also provide a method of making an improved pool. The pool can comprise an unitary sidewall joined to a floor portion. The unitary sidewall can be constructed from one piece of material, and can have fewer seams than traditional pools, thereby reducing the likelihood that that pool will rupture and leak. In some embodiments, since the pool has fewer seams than traditional pools, fewer manufacturing steps are required to make the pool. This can increase manufacturing speed and decrease cost.